Analisis Risiko Operasional Gudang Menggunakan Failure Mode and Effect Analysis (Studi Kasus: Gudang Konsolidasi Ekspor PT XYZ) - Mutzahidan Akmal; Gita Kurnia (JURNAL REKAYASA SISTEM INDUSTRI, 2023)
PT XYZ is a national-scale company located in Jakarta, Indonesia, providing logistics services such as warehousing for export consolidation. The warehouse activities are not considered optimal because many processes do not run according to the system. Hence, there are failures in several activities, which would reduce customer satisfaction. One of the reasons is that no risk management system has been applied in the company yet. This study conducts a company risk analysis and proposes recommendations for the identified critical risks using Failure Mode and Effect Analysis (FMEA). The risk priority number calculation result shows five critical risks: inbound control, inventory control, outbound control, supplier relation and warehouse operational process. Several recommendations are also formulated to reduce critical risks.